The Update Treatments of Psoriasis - Nuntiyagul, Witaya (Journal of Health Science of Thailand, 2018)
Psoriasis has long been a common chronic inflammatory hyperproliferative skin disease in dermatological practice. The treatment of psoriasis has many methods including topical and systemic treatments but unacceptable toxicity is the main problem. The biologic therapy was approached with satisfactory result but more clinical trials should be done to confirm the effectiveness of biologic agents. Currently, the update treatments of psoriasis including adverse effects were reviewed.